17β-estradiol activation of dorsal hippocampal TrkB is independent of increased mature BDNF expression and is required for enhanced memory consolidation in female mice. (March 2021) - Gross, Kellie S.; Alf, Randie L.; Polzin, Tiffany R.; Frick, Karyn M.
Abstract: The potent estrogen 17β-estradiol (E2 ) is known to enhance hippocampal memory and plasticity, however the molecular mechanisms underlying these effects remain unclear. Brain derived neurotrophic factor (BDNF) and its receptor tropomyosin receptor kinase B (TrkB) are regulated by E2, but the potential mechanistic roles of neurotrophic signaling in E2 -induced enhancement of memory are not well understood. Here, we examined the effects of hippocampal TrkB signaling on E2 -induced enhancement of memory consolidation in the object placement and recognition tasks. Bilateral infusion of the TrkB antagonist ANA-12 into the dorsal hippocampus of ovariectomized female mice blocked E2 -induced enhancement of memory consolidation, supporting a role for TrkB-mediated signaling in estrogenic regulation of memory. Although dorsal hippocampal E2 infusion increased levels of phospho-TrkB and mature BDNF (mBDNF) in the dorsal hippocampus within 4–6 h, E2 -induced increases in hippocampal mBDNF expression were not required for hippocampal TrkB activation and were not inhibited by TrkB antagonism. Thus, E2 regulates TrkB signaling to facilitate memory consolidation in a manner independent of mBDNF expression. Together these results provide the first direct evidence that E2 modulation of hippocampal TrkB signaling is required for its beneficial effects on memory consolidation and provide additional characterization of the ways in which TrkB/BDNF signaling is regulated by E2 in the hippocampus. Highlights: TrkB antagonist ANA-12 dose-dependently inhibits hippocampal memory consolidation. Hippocampal TrkB activity is required for estradiol to enhance memory consolidation. Estradiol increases hippocampal TrkB activity prior to increased BDNF expression. Estradiol-induced expression of hippocampal BDNF does not depend on TrkB activity.